Problematyka sprawności mówienia we wczesnoszkolnej edukacji językowej w świetle współczesnych niemieckojęzycznych badań empirycznych - Wieszczeczyńska, Ewa (Neofilolog, 2010)
The main goal of this paper is to evaluate recent empirical studies conducted in the German environment which concern the processes of foreign language acquisition by young children in their early school education. The results of these new studies led to the development of new teaching strategies based on the interaction between the teacher and the young learners. Different aspects of the studies reported in the paper are now subject to a widespread debate and they deserve attention in our educational context as well, since Polish schools resemble German ones in many respects. Therefore, the critical overview presented here can be seen as an inspiration for a new research agenda in the area of second language research and teaching methodology for that age group. Moreover, from the practical point of view, it opens new options in developing new teaching methods and teaching materials for young foreign language learners in Polish schools.